2006
DOI: 10.1016/j.jmb.2005.11.077
|View full text |Cite
|
Sign up to set email alerts
|

FGFR3 Dimer Stabilization Due to a Single Amino Acid Pathogenic Mutation

Abstract: Mutations in the transmembrane (TM) domains of receptor tyrosine kinases (RTKs) have been implicated in the induction of pathological phenotypes. These mutations are believed to stabilize the RTK dimers, and thus promote unregulated signaling. However, the energetics behind the pathology induction has not been determined. An example of a TM domain pathogenic mutation is the Ala391-->Glu mutation in fibroblast growth factor receptor 3 (FGFR3), linked to Crouzon syndrome with acanthosis nigricans, as well as to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

24
195
3

Year Published

2006
2006
2024
2024

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 98 publications
(222 citation statements)
references
References 53 publications
24
195
3
Order By: Relevance
“…For probes restricted to membranes, FRET between unbound diffusible donors and acceptors is more likely (34 -36) and has been quantified by multiple approaches (2,37). For the present study, the minimum FRET observed between YFP-and mCherry-PLB in the presence of a large excess of CFP-PLB competitor (Fig.…”
Section: Discussionmentioning
confidence: 87%
“…For probes restricted to membranes, FRET between unbound diffusible donors and acceptors is more likely (34 -36) and has been quantified by multiple approaches (2,37). For the present study, the minimum FRET observed between YFP-and mCherry-PLB in the presence of a large excess of CFP-PLB competitor (Fig.…”
Section: Discussionmentioning
confidence: 87%
“…On the other hand, the A393E mutation increases the fraction of FGFR3 dimers resulting from dimer stabilization, measured by the change in the free energy of dimerization. 35,47 In addition, BernardPierrot et al 46 demonstrated that FGFR3b-S249C was able to transform NIH-3T3 cells, inducing their anchorage-independent growth and tumor transformation when injected subcutaneously into nude mice, with the transforming properties classically attributed to oncogenes.…”
Section: Discussionmentioning
confidence: 99%
“…The measured effect of the order of -1 kcal/mole is similar to results obtained for a model system comprising the isolated FGFR3 TM domains in bilayers of different composition, demonstrating that the Ala391Glu mutation stabilizes the FGFR3 TM domain dimer by -1.3 ± 0.2 kcal/mole. 41 In addition, computational and experimental studies of the structure of the isolated Neu/ErbB2 and FGFR3 TM domain dimers demonstrate dimer stabilization via Glu-mediated hydrogen bonding. 9,12,14,[41][42][43] Taken together, these results strongly suggest that hydrogen bonds stabilize the mutant Neu/Val664Glu and Neu_FGFR3/Ala391Glu receptors in mammalian cells, a mechanism that was originally proposed 18 years ago, 42 but has been debated ever since.…”
Section: Structure Of Rtk Tm Dimersmentioning
confidence: 99%
“…41 In addition, computational and experimental studies of the structure of the isolated Neu/ErbB2 and FGFR3 TM domain dimers demonstrate dimer stabilization via Glu-mediated hydrogen bonding. 9,12,14,[41][42][43] Taken together, these results strongly suggest that hydrogen bonds stabilize the mutant Neu/Val664Glu and Neu_FGFR3/Ala391Glu receptors in mammalian cells, a mechanism that was originally proposed 18 years ago, 42 but has been debated ever since. Furthermore, the results suggest that an increase of the order of -1 kcal/mole may be sufficient to transform normal RTK signaling processes into pathogenic processes.…”
Section: Structure Of Rtk Tm Dimersmentioning
confidence: 99%